The Effect of Servant Leadership and Motivation on Employee Performance: The Mediating of Work Engagement - Majid, Muhammad Bigar Al; Puspita, Rosana Eri (Mabny: Journal of Sharia Management and Business, 2024)
This research aims to determine the influence of Servant Leadership and Work Motivation on Employee Performance with Work Engagement as an Intervening Variable. The subjects of this research were 52 employees of the Trans Central Java Bus under the auspices of PT Mulia Orda Serasi. The author uses quantitative methods in this research where data is obtained through questionnaires. The data analysis that has been carried out shows that: (1) Servant leadership has a positive and insignificant influence on the performance of Trans Central Java bus employees. (2) Work motivation has a positive and significant influence on the performance of Trans Central Java bus employees. (3) Servant leadership has a positive and significant influence on the work engagement of Trans Central Java bus employees. (4) Work motivation has a positive and significant influence on the work engagement of Trans Central Java bus employees. (5) Work engagement has a positive and significant influence on the performance of Trans Central Java bus employees. (6) Work engagement can mediate the influence of servant leadership on the performance of Trans Central Java bus employees. (7) Work engagement 0can mediate the influence of work motivation on the performance of Trans Central Java bus employees.